Advances of bispecific antibodies using/application in dermatology: a review - Zhang, Ting; Liu, Yang; Liew, Pei Xiong; Zhang, Yu; Zhao, Zuotao (Frontiers in Allergy, 2025)
Bispecific antibodies represent an important innovation in the field of biomedicine in recent years. Compared to monoclonal antibodies, their specific structure enables a single antibody molecule to bind to two different antigens simultaneously. This characteristic endows bispecific antibodies with more functions, regulating multiple signal pathways simultaneously, enhancing the therapeutic effect, and by infusion of targeted tumor antigens and drug carriers in advance, the contact time between the drug and normal tissues is reduced, and the toxic side effects are greatly reduced. They have shown promising application prospects, especially in dermatology and other fields. This article reviews the basic concepts of bispecific antibodies and their potential application in the treatment of skin diseases, including inflammatory skin diseases, skin tumors, and infectious skin diseases. The aim is to explore the current application status and future development directions of bispecific antibodies in dermatology, so as to provide references for related research and clinical practice.